2022
DOI: 10.3390/su141811385
|View full text |Cite
|
Sign up to set email alerts
|

E-Learning and Sustainability of Pondok Schools: A Case Study on Post-COVID-19 E-Learning Implementation among Students of Pondok Sungai Durian, Kelantan, Malaysia

Abstract: In almost every corner of the world, the COVID-19 pandemic disrupted daily life and work. During the pandemic, e-learning technologies were critical and were the ideal alternative to the traditional classroom setting. Throughout the COVID-19 pandemic, Malaysia’s education system placed heavy emphasis on online learning in connection with new technological advances as a mode of interaction to substitute direct conventional instruction. The aim of this research is to determine student acceptability of e-learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Motivation is an important factor that affects student attitudes and learning behaviour at all levels of education. Previous studies have shown that the effectiveness of technology adoption in the field of education greatly depends on student motivation to use the system [1,2,17,18]. A study by Rahman, et al [2] emphasises that student motivation is one important indicator in helping students to understand the importance of continuing their studies online.…”
Section: Students' Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…Motivation is an important factor that affects student attitudes and learning behaviour at all levels of education. Previous studies have shown that the effectiveness of technology adoption in the field of education greatly depends on student motivation to use the system [1,2,17,18]. A study by Rahman, et al [2] emphasises that student motivation is one important indicator in helping students to understand the importance of continuing their studies online.…”
Section: Students' Motivationmentioning
confidence: 99%
“…Previous studies have shown that the effectiveness of technology adoption in the field of education greatly depends on student motivation to use the system [1,2,17,18]. A study by Rahman, et al [2] emphasises that student motivation is one important indicator in helping students to understand the importance of continuing their studies online. Lamb, et al [19] suggest that student motivation to learn in an online environment relates to learning outcomes.…”
Section: Students' Motivationmentioning
confidence: 99%
See 3 more Smart Citations